Upaya Meningkatkan Hasil Belajar Matematika Dengan Menggunakan Model Pembelajaran Student Teams Achievement Division - Sumini Sumini (JURNAL GLOBAL EDUKASI, 2017)
Abstract: The purpose of this study is to improve the results of mathematics learning by using student teams achievement division model. The subjects of the study were students of class III B SD Negeri 013827 Persatuan academic year 2016/2017 with the number of students in one class that is 30 children. From research data known in cycle I the average value obtained for 79.00 with the percentage of learning mastery of 76.67%. In the second cycle there is an increase in learning outcomes, the average value to 93.33 with a percentage of 96.67% completeness. Based on the research that has been done, it can be concluded that with the implementation of cooperative model learning model Student Teams Achievement Division as a model of learning can improve learning outcomes Mathematics on materials Know the value of money in class III B SD Negeri 013827 Persatuan. Keywords: student teams achievement division, value for money Abstrak: Tujuan penelitian ini adalah untuk meningkatkan hasil belajar matematika dengan menggunakan model pembelajaran student teams achievement division. Subyek penelitian adalah siswa kelas III B SD Negeri 013827 Persatuan tahun ajaran 2016/2017 dengan jumlah siswa dalam satu kelas yaitu 30 anak. Dari data penelitian diketahui pada siklus I nilai rata-rata diperoleh sebesar 79,00 dengan persentase ketuntasan belajar sebesar 76,67%. Pada siklus II terjadi peningkatan hasil belajar, nilai rata-rata menjadi 93,33 dengan persentase ketuntasan sebesar 96,67%. Berdasarkan penelitian yang telah dilakukan, dapat disimpulkan bahwa dengan penerapan pembelajaran model kooperatif tipe Student Teams Achivement Division sebagai model pembelajaran dapat meningkatkan hasil belajar Matematika pada materi Mengenal nilai uang di kelas III B SD Negeri 013827 Persatuan. Kata kunci: student teams achievement division